PENGARUH TINGKAT PENDAPATAN DAN PENGELOLAAN DANA ZAKAT TERHADAP KEPATUHAN MASYARAKAT MEMBAYAR ZAKAT DI KABUPATEN BIREUEN - Murhaban Murhaban; Merawati Merawati (Department of Accounting, Faculty of Economics & Business, 2018)
This study aims to determine the effect of the income level and management of zakat funds on the community compliance to pay zakat in Bireuen Regency. The sampling technique used is probability sampling technique with the number of respondents as many as 62 people. The data used in this study is in the form of primary data in the form of questionnaires. The analytical method used is multiple linear regression analysis with the help of SPSS program. The results of this study indicate that the level of income has a significant effect on the community compliance to pay zakat in Bireuen Regencyt and the management of zakat funds has no significant effect on the community compliance to pay zakat in Bireuen Regency.